Heart failure hospitalizations and clinical outcomes in patients undergoing tricuspid transcatheter edge-to-edge repair: insights from EuroTR - Tomasoni, Daniela; Adamo, Marianna; Hausleiter, Jörg; Pezzola, Elisa; Kresoja, Karl-Patrik; von Stein, Jennifer; Fortmeier, Vera; Pauschinger, Christoph; Rottbauer, Wolfgang; Kassar, Mohammad; Goebel, Bjoern; Denti, Paolo; et al. (European journal of heart failure, 2025)
Aims To assess the prevalence, prognostic significance, and predictors of heart failure hospitalization (HFH) before and after tricuspid transcatheter edge-to-edge repair (T-TEER) in a large real-world cohort of patients with tricuspid regurgitation (TR). Methods and results Data from the European Registry of Transcatheter Repair for Tricuspid Regurgitation (EuroTR registry) were analysed. Among 1000 patients undergoing T-TEER for symptomatic TR, 361 (36.1%) had no HFH, 459 (45.9%) had one single HFH, and 180 (18.0%) had multiple HFH the year before T-TEER. Patients with any HFH had more severe heart failure compared with those without. Procedural success (residual TR ≤2) did not differ between patients with single, multiple, or no HFHs before T-TEER. Multivariable analysis showed that a history of HFH was associated with an increased mortality risk (adjusted hazard ratio [HR] 1.51, 95% confidence interval [CI] 1.11-2.06 for single vs. no HFH; adjusted HR 1.63, 95% CI 1.15-2.31 for multiple vs. no HFH), and a higher risk of the combined endpoint of all-cause mortality or HFH. HFH risk decreased by 72% in the 1 year following T-TEER compared to the previous year. Procedural success was the sole independent predictor for reducing HFHs. Conclusions In the EuroTR cohort, a history of HFH was highly prevalent and associated with worse clinical outcomes. Among high-risk patients with symptomatic TR, T-TEER significantly lowered HFH risk, with residual TR grade ≤2 being the key predictor for reduced HFH incidence.